Bipolar High Voltage DC Generator ±100 kV 5 mA - K.Tonmitra, K.Tonmitra; A.Suksri, A.Suksri (Engineering and Applied Science Research, 2013)
This paper presents the design and construction of Bipolar high voltage DC generator rated ±100 kV 5 mA. The high voltage DC generator rated 200 kV 5 mA is constructed by using the basic of 2 stage Cockcroft-Walton circuit for a verification test against the Bipolar high voltage DC generator. The bipolar high voltage DC Generator ±100 kV 5 mA is constructed by altering the connection of the single stage Cockeroft-Walton into bipolar circuit. The high voltage diode and capacitor were developed at high voltage laboratory specifically for this research. Test and results confirms that the bipolar high voltage DC generator has the higher voltage efficiency than the DC generator as much as 94.3% while the conventional Cockeroft-Walton was able to achieve at 86.24%. In the same time, the ripple voltage as well as the voltage drop has reduced much further at the same input voltage value.